Kindergarten Management System - Kathiraveloo, Mathushini; Othman, Muhaini Binti Othman (Applied Information Technology And Computer Science, 2024)
The Kindergarten Management System, a web-based solution, addresses the challenges faced by administrators, teachers, and parents at Kindergarten Khalifah Junior UTHM. The existing manual record-keeping system, primarily reliant on Microsoft Excel, necessitates a more efficient and streamlined approach.This project aims to design and implement a structured approach design kindergarten management system with a web-based interface, focusing on enhancing student and teacher information management. The scope encompasses the target users of the system, ensuring it meets the specific needs of administrators, teachers, and parents.Employing the prototyping model, this project integrates prototype methods into critical phases of the system development life cycle (SDLC). The approach spans planning, analysis, design, prototype development, and implementation, facilitating a systematic and iterative process.The Kindergarten Management System, enhanced through prototyping, ensures efficient data management and user acceptance. Notably, it simplifies administrative processes, including the enrollment of new teachers and students, contributing to overall system robustness.The system maintains comprehensive student data, academic records, and payment information securely. SMS notifications to parents about financial obligations enhance communication. The computerized data management system prevents potential data loss and disposal. Future work should focus on continuous improvement and adapting to evolving kindergarten management needs.